1994
DOI: 10.1029/93ja02015
|View full text |Cite
|
Sign up to set email alerts
|

Response of the thermosphere and ionosphere to geomagnetic storms

Abstract: Four numerical simulations have been performed, at equinox, using a coupled thermosphere‐ionosphere model, to illustrate the response of the upper atmosphere to geomagnetic storms. The storms are characterized by an increase in magnetospheric energy input at high latitude for a 12‐hour period; each storm commences at a different universal time (UT). The initial response at high latitude is that Joule heating raises the temperature of the upper thermosphere and ion drag drives high‐velocity neutral winds. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
815
3
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 800 publications
(876 citation statements)
references
References 38 publications
56
815
3
2
Order By: Relevance
“…However, this is contrary to the predictions obtained in some recent storm modelling studies using major thermospheric general circulation models (Rishbeth et al, 1987;Crowley et al, 1989;Fuller-Rowell et al, 1991, 1994. This con¯icting result is also discussed by Burns et al.…”
Section: Thermospheric Compositioncontrasting
confidence: 64%
See 1 more Smart Citation
“…However, this is contrary to the predictions obtained in some recent storm modelling studies using major thermospheric general circulation models (Rishbeth et al, 1987;Crowley et al, 1989;Fuller-Rowell et al, 1991, 1994. This con¯icting result is also discussed by Burns et al.…”
Section: Thermospheric Compositioncontrasting
confidence: 64%
“…More recent work of Fuller-Rowell et al (1994) and Burns et al (1995a, b) provoked the present investigations. Their results led them to conclude that there is a signi®cant enhancement of the [O]/[N 2 ] ratio in the evening sector of the mid-latitude winter hemisphere, providing an essential contribution to the positive storm e ect there.…”
Section: Introductionmentioning
confidence: 69%
“…The negative storm effects occurred often during the main and recovery phases of storms (Abdu, 1997;Cander and Mihajlovic, 2005). Negative storm effects at high and middle latitudes are caused primarily by neutral composition changes due to the upwelling of molecular-rich air to higher altitudes driven by storm-time enhanced Joule heating (Mayr, Harris, and Spencer, 1978;Burns et al, 1995;Fuller-Rowell et al, 1994). The negative storm effects around the geomagnetic Equator are more closely related to changes in transportation caused by penetration electric fields (Lei et al, 2008c;Wang et al, 2010), as well as changes in neutral composition at later times during strong storms (Prölss, 1995;Buonsanto, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The equatorward divergent¯ow from high latitudes causes upwelling through the pressure surfaces and increases of mean molecular mass ProÈ lss, 1987;Burns et al, 1991). The region of increased mean molecular mass has been termed a composition``bulge,'' and it has been recently shown that the bulge can be transported by the background and storm-time wind ®elds (Fuller-Rowell et al, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that individual storms show large deviations from the average behavior. The dependence of the storm-time ionosphere to both local time and season can be explained as a response to neutral composition changes and their movement by the global wind ®eld (Fuller-Rowell et al, 1994.…”
Section: Introductionmentioning
confidence: 99%